The position of the law and the judiciary on cybercrime (Syriac) Comparative study (Journal of the College of Basic Education, 2022)
Cyber ​​crime, that is, the virtual crime that takes place in electronic space emanating from (Cyber ​​Space), that is, the virtual or virtual space, and William Visbon is the first to use this term in his novel in 1984.Then came the Tenth Conference of the United Nations held in Vienna in the year 2000 to confirm this designation for electronic crimes that have spread recently due to the spread of the Internet and the opening of many areas to benefit from it, which was imposed by these modern technologies and the abundant flow of information that can be used for the benefit of humanity and at the same time there are damages that occurred during In recent years, these crimes have become one of the most dangerous types of crimes of the era. The perpetrators of the crime have moved from its traditional forms and means to electronic ones.